Radiation dose in cerebral angiography and flat detector CT applications in neuroradiology - Struffert, Tobias; Lang, Sabine; Scholz, R.; Hauer, M.; Dörfler, Arnd (Radiologe, 2015)
Flat detectors (FD) have completely replaced image intensifiers in angiography. Due to this development not only the image quality of 2D digital subtraction angiography series (2-D-DSA) could be improved but also the acquisition of computed tomography (CT)-like cross-sectional images (FD-CT) within the angio suite became feasible. These techniques are now being used in daily clinical routine. Only little information about effective doses of these applications to patients has been published in the literature. We describe the effective patient dose of current applications in the field of angiography and demonstrate strategies to minimize the dose to the patient. In addition, we compare FD-CT applications to standard multislice CT applications.
EVALuna2:22998